2020
DOI: 10.31004/basicedu.v4i2.374
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Bahan Ajar Tematik Terpadu dengan Strategi Question Student Have di Sekolah Dasar

Abstract: Penelitian ini bertujuan untuk menghasilkan bahan ajar tematik dengan strategi Question Student Have untuk pendidik kelas IV yang valid, praktis, dan efektif. Penelitian ini menggunakan penelitian pengembangan berdasarkan model 4D (Define, Design, Develop dan Disseminate). Kevalidan dilhat dari segi isi, bahasa, penyajian, kegrafikaan dan RPP, keseluruhan 3,54 dengan kategori sangat valid. Pratikalitas bahan ajar dilihat dari respon pendidik dengan rata-rata 90% respon peserta didik 90 %.  Dapat disimpulkan ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 0 publications
0
19
0
19
Order By: Relevance
“…This research is supported by relevant previous researches, namely research conducted by (Lestari et al, 2017) those who obtained the mean validity with a percentage of 88.6% were categorized as very valid for student books and the mean validity with a percentage of 86.8% was categorized as very valid for teacher books. The next relevant research is research conducted by (Weriyanti et al, 2020) who obtained the validity of teaching materials with an average of 3.56, including the very valid category and research conducted by (Yati & Amini, 2020) who obtained the validity of teaching materials with an average of 4.24, including the very valid category.…”
Section: Introductionmentioning
confidence: 99%
“…This research is supported by relevant previous researches, namely research conducted by (Lestari et al, 2017) those who obtained the mean validity with a percentage of 88.6% were categorized as very valid for student books and the mean validity with a percentage of 86.8% was categorized as very valid for teacher books. The next relevant research is research conducted by (Weriyanti et al, 2020) who obtained the validity of teaching materials with an average of 3.56, including the very valid category and research conducted by (Yati & Amini, 2020) who obtained the validity of teaching materials with an average of 4.24, including the very valid category.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, from the results of the needs analysis, it was also found that what students currently need are teaching materials that make it easier for students to understand the material being studied as well as teaching materials found by students in everyday life because that is why. The importance of teaching materials in the learning process requires teachers to be able to develop teaching materials that are in accordance with the needs of students, implementing the curriculum, not depending on texts and government aid packages, and in accordance with the characteristics of students (Andani & Yulian, 2018;Cloonan & Fingeret, 2020;Mayarnimar & Taufina, 2017;Weriyanti et al, 2020). With the existence of teaching materials in accordance with the curriculum, needs and characteristics will be able to increase student motivation and students can obtain learning in accordance with the development of science and technology (Suzuki et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This can be caused by the lack of teaching materials that support the implementation of learning. Currently, the existing teaching materials have not been able to develop students' courage and skills in asking questions and opinions (Weriyanti et al, 2020). Currently, the learning process only uses teaching materials, namely student books, which need to be revised and added material according to student needs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) Peserta didik kurang mampu bekerja sama dan mengembangkan sikap sosial nya dengan teman lain. Hal tersebut terlihat dalam diskusi kelompok yang dilaksanakan, di mana hanya beberapa orang peserta didik yang mau bekerja sama dengan teman satu kelompok dan banyak yang bekerja secara individu (Weriyanti, Firman, Taufina, & Zikri, 2020). 4) Kemudian ketika diminta untuk menjawab pertanyaan peserta didik terlihat sering bertanya dan melihat ke jawaban temannya.…”
Section: Pendahuluanunclassified